Intervensi Model Pendidikan dan Komunitas tentang Influenza Menurut Mahasiswa Kedokteran dan Keperawatan - Andyana Sabtisan; Priska Yunianti; Bryani Titi Santi; Dwi Jani Juliawati; Elisabeth Rukmini (Asosiasi Institusi Pendidikan Kedokteran Indonesia, 2016)
Background: Medical awareness and clinical management of seasonal influenza remains limited in Indonesia. As future health workers, nursing students’ and medical students’ knowledge, attitude, and practice regarding influenza and influenza vaccine are important to make patients have better understanding about influenza. We explored their ideas about community intervention and education models regarding influenza and influenza vaccine. The aims of this study were to obtain nursing students’ ideas about community intervention models and medical students’ idea about education models regarding influenza and influenza vaccine.Method: A qualitative study using in-depth interview was conducted towards 10 nursing students and 10 medical students to explore their opinions and ideas about community intervention and education models regarding influenza and influenza vaccine.Results: Nursing students’ ideas for community intervention models were varied. Most of them mentioned poster, leaflet, workshop, counselling, and free influenza vaccination. There were also some interesting ideas, such as influenza handbook, influenza educational song, influenza car campaign, and popular science article about influenza. As for medical students, the education model they proposed was mostly seminar, workshop, pre-clinic training, and visual media such as poster and video.Conclusion: The study highlights the needs to educate future health workers about influenza and influenza vaccine to improve knowledge, practice and attitudes. Innovative and up-to-dateintervention models regarding influenza and influenza vaccine are needed to improve the health workers’ quality.